Pengaruh penambahan gula terhadap kualitas vinegar dari air kelapa - Sri Agustini, Silfia, (Balai Riset dan Standardisasi Industri Palembang, 2014)
Vinegar is an organic acid compound known as a preservative acids, flavoring and aroma in food. Vinegar can be made from sugar containing substrate which can be obtained from a various of materials such as fruits and coconut water. This research intended to maximize the utilisation of coconut water as raw material in making natural vinegar. Coconut water vinegar is a natural product that is produced from fermentation of coconut water substrate enriched with sugar. Research applied completely randomized design where the sugar addition as treatment consist of 6%, 8%, 10%, 12%, 14%. The effect of sugar addition on the quality of coconut water vinegar examined according to SNI requirement and sensories test for taste and aroma by 20 panelist. The results showed that treatment of 12% adding sugar gave the best results with a level of acetic acid, pH and sugar concentration were 8.22%, 3.80, 5.82% respectively. Contamination Pb was not detected, Fe was 0.065 ppm, arsenic was 0.046 ppm. Score for organoleptic test for taste and aroma was 3.59 and 3.78 out of 5 respectively. Key words: Vinegar, coconut water, sugar, pH AbstrakVinegar adalah senyawa kimia asam organik yang dikenal sebagai pengawet, pemberi rasa asam dan aroma dalam makanan. Vinegar dapat dibuat dari substrat yang mengandung gula dapat diperoleh dari berbagai macam bahan seperti buah-buahan dan air kelapa. Penelitian ini bertujuan untuk memanfaatkan air kelapa sebagai bahan baku pembuatan vinegar alami. Vinegar air kelapa merupakan produk alami yang dihasilkan dari fermentasi alkohol dengan substrat air kelapa yang diperkaya dengan gula. Penelitian menggunakan rancangan acak lengkap dengan konsentrasi penambahan gula 6%, 8%, 10%, 12%, 14% sebagai perlakuan. Hasil penelitian menunjukkan bahwa perlakuan penambahan gula 12% memberikan hasil terbaik dengan kadar asam asetat 8,22%; pH 3,80; kadar gula 5,82%, cemaran logam Pb tidak terdeteksi, Fe (0,065ppm), cemaran Arsen (0,046ppm). Uji organoleptik oleh 20 orang panelis terhadap rasa mendapatkan 3,59 dan aroma 3,78. Kata Kunci: Vinegar, air kelapa, gula, pH